Hal-Hal Yang Ada Hubungan Dengan Rhinitis Alergi Pada Penderita Di Beberapa Lokasi Di Wilayah Asia Periode Tahun 2012 Sampai Dengan Tahun 2021 - Tangkeallo, Elitha Lorani Patiung; Madjid, Baedah; Hasbullah, Ayu Ameliyah (Bosowa Medical Journal, 2025)
Allergic rhinitis is a clinical condition by humoral immunity activation, mediated by IgE (type 1 hypersensitivity) in response to environmental antigens resulting in inflammation of the upper respiratory tract causing abnormalities in the nose with symptoms of sneezing, rhinorrhea, itching, and congestion. To find out things that have to do between allergic rhinitis in patients in several locations in the Asian region from 2012 to 2021. The research method used is a systematic review by synthesizing the results obtained from ten scientific research journals with a case control research design. The results of the ten studies analyzed showed that there are things related to allergic rhinitis in patients in several locations in the Asian region from 2012 to 2021, namely there was a significant relationship between age (p-value 0.000), exposure to cigarette smoke (p-value 0.000), exposure to animal hair (p-value 0.003), and history of asthma (p-value 0.000) and there was no significant relationship between gender (p-value 0.391) and family history (p-value 0.090) on the incidence of allergic rhinitis. Conclusion: Allergic rhinitis in patients in several locations in the Asian region from 2012 to 2021 has a significant related with age, exposure to cigarette smoke, exposure to animal dander and history of asthma and has a non-significant related with gender and family history